The FINANCIAL LITERACY AND FINANCIAL PERFORMANCE OF BUSINESSES OF PERSONS WITH DISABILITIES IN UGANDA: A CASE OF NUDIPU-iSAVE GROUP BENEFICIARIES, NORTHERN DIVISION, KAMULI DISTRICT: Financial performance of businesses of persons with disabilities - Wolukawu, Ambrose; MALUNDA, PAUL (Student's Journal of Health Research Africa, 2025)
The study examined the effect of financial literacy on the financial performance of businesses of Persons with Disabilities in Uganda. A case of NUDIPU-iSAVE group beneficiaries, Northern Division, Kamuli District. The study’s specific objectives were; to examine the effect of budgeting literacy, saving literacy and debt management literacy on the financial performance of businesses of Persons with Disabilities under NUDIPU-iSAVE Economic Empowerment Model Northern Division, Kamuli District. The study was underpinned by theory of planned behavior. The study adopted a survey design that employed quantitative and qualitative methods targeting a population of 221 with a sample size of 152 selected and of these respondents, 127 responded (83.6% response rate). This sample was selected using stratified random, purposive sampling techniques and census. Data were collected using a researcher administered questionnaire, Focus Group Discussions, face to face interviews with the key infromansts and document review. Data were analysed using descriptive and inferential statistics (regression analysis in particular) in SPSS 29.0. The study established that budgeting literacy, savings literacy and debt management literacy all have a significant effect on financial performance of businesses of PwDs. The study concluded that improving budgting literacy, saving literacy and debt management literacy would improve the financial performance of businesses of PwDs. It was recommended that project management should improve on the weak aspects of each financial literacy aspects, namely budgeting, savings and debt management literacy to enhance they financial performance.However, it was recommended that priority should be given to savings literacy, followed by budgeting literacy and debt management literacy owing to the relative prediction strength business performance. Further research can be conducted to establish an ideal framework for enhancing the economic and technical sustainability of NUDIPU-iSave Economoc Empwoernment Model.